Lethal factor VII deficiency due to novel mutations in the F7 promoter: Functional analysis reveals disruption of HNF4 binding site - Giansily-Blaizot, Muriel; Lopez, Estelle; Viart, Victoria; Chafa, Ouerdia; Tapon-Bretaudière, Jacqueline; Claustres, Mireille; Taulan, Magali (Thrombosis and Haemostasis, 2012)
Hereditary factor VII (FVII) deficiency is a rare autosomal recessive disorder. Deleterious mutations that prevent the synthesis of any amount of functional FVII have been associated with life-threatening haemorrhage in neonates. Here we report two infants, of Maghrebian origin, who suffered a fatal spontaneous cerebral haemorrhage. Investigation of the molecular basis for their severe FVII deficiency revealed novel mutations in a homozygous state within the F7 gene promoter: a single nucleotide substitution (c.-65G>C) and a 2bp deletion (c.-60_-59delTT). To determine whether these promoter variants were responsible for the FVII deficiency, computer–assisted sequence analyses were performed. The data predicted a disrupted binding of both HNF4 and COUP-TF transcription factors with each variant. Concordantly, experimental results revealed an altered HNF4-induced transactivation in the promoter mutated variants. The execution of functional tests is critical to ensuring a complete understanding of the effect of any promoter mutant on FVII deficiency. Only then can an accurate molecular diagnosis be made and further genetic counselling and prenatal diagnosis be offered.
Keywords: FVII deficiency; promoter mutation; HNF4; COUP-TF1